Organisational culture and entrepreneurial orientation: An orthogonal perspective of individualism and collectivism. (March 2019) - Lee , Younggeun; Howe, Michael; Kreiser , Patrick M
This study contributes to the existing literature regarding the relationship between culture and entrepreneurship. Building upon the precepts of institutional theory, we examine the influence of organisational culture on firm-level entrepreneurial orientation. While entrepreneurship researchers have emphasised the importance of entrepreneurial orientation for firms, the influence of organisational culture in supporting the incidence of entrepreneurial orientation has not been adequately studied. In an effort to contribute to this emergent area of inquiry, we consider the role of two key dimensions of organisational culture − individualism and collectivism – in facilitating entrepreneurial orientation. In doing so, we illustrate the utility of adopting an orthogonal conceptualisation of these cultural dimensions rather than the commonly held unidimensional formulation. We use polynomial regression and response surface methodology to investigate the effects of both dimensions of organisational culture on entrepreneurial orientation. Using Korea as the main context of the study, we support our hypotheses using data collected from 406 Korean small- and medium-sized enterprises.